2009
DOI: 10.1007/s10979-008-9133-0
|View full text |Cite
|
Sign up to set email alerts
|

Can jurors recognize missing control groups, confounds, and experimenter bias in psychological science?

Abstract: This study examined the ability of jury-eligible community members (N = 248) to detect internal validity threats in psychological science presented during a trial. Participants read a case summary in which an expert testified about a study that varied in internal validity (valid, missing control group, confound, and experimenter bias) and ecological validity (high, low). Ratings of expert evidence quality and expert credibility were higher for the valid versus missing control group versions only. Internal vali… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

8
68
3

Year Published

2010
2010
2022
2022

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 48 publications
(82 citation statements)
references
References 35 publications
8
68
3
Order By: Relevance
“…Previous research suggests that potential jurors are often unable to detect flaws in scientific research (McAuliff, Kovera, & Nunez, 2009). Although the current study does not specifically address whether the technology used is flawed per se, as reviewed previously, there are many limitations to fMRI lie detection that may or may not be evident to potential jurors.…”
Section: The Current Studymentioning
confidence: 99%
“…Previous research suggests that potential jurors are often unable to detect flaws in scientific research (McAuliff, Kovera, & Nunez, 2009). Although the current study does not specifically address whether the technology used is flawed per se, as reviewed previously, there are many limitations to fMRI lie detection that may or may not be evident to potential jurors.…”
Section: The Current Studymentioning
confidence: 99%
“…ELM has been employed as a theoretical framework for understanding how jurors process complicated trial information. For instance, McAuliff, Kovera, and Nunez (2009) hypothesized that mock jurors exposed to an expert witness's research study might engage in central processing (as indicated by their ability to differentiate an internally invalid from an internally valid study) and/or peripheral processing (as indicated by reliance on the study's ecological validity as a heuristic cue) in judging the quality of the study and the expert's testimony. The researchers found limited evidence of central processing (mock jurors rated study quality lower when there were missing control groups but not when there were confounds or experimenter bias) but no effect on verdicts, and they found no tendency to resort to peripheral cues in lieu of more systematic thinking about the evidence.…”
mentioning
confidence: 99%
“…1 However, given the limited knowledge of legal professionals about factors that affect the reliability if eyewitness testimony and the results of studies suggesting that trial judges and jurors may have difficulty in distinguishing between science and junk science (Kovera, Russano, & McAuliff, 2002;McAuliff, Kovera, & Nunez, 2009), the court may have problems complying with the Daubert recommendations, and the issue boils down to the appointment of qualified eyewitness expert witnesses. 2 Who are eyewitness experts?…”
mentioning
confidence: 99%